Mechanical Ventilation and Coronavirus Disease 2019: A Case-Control Analysis of Clinical Characteristics, Lung Mechanics, and Mortality. (26th March 2021) - Abu Sayf, Alaa; Fadel, Raef; Scott, Ashley; Al Bizri, Layla; Kong, Wing Tai; Rezik, Mohamed; Joyce, Katherine; Alalwan, Yusuf; Dabaja, Mohamed; Nair, Sashi; Modi, Krishna; Brar, Indira; et al.
Abstract : Objectives: To investigate the differences in clinical course, ventilator mechanics, and outcomes of patients with coronavirus disease 2019 secondary to acute respiratory distress syndrome infection compared with a historical cohort of acute respiratory distress syndrome. Design: Comparative case-control study. Setting: Multicenter, comprehensive tertiary healthcare facility in Detroit, MI. Patients/Subjects: Adult patients hospitalized with coronavirus disease 2019 secondary to acute respiratory distress syndrome infection were compared with patients hospitalized with acute respiratory distress syndrome prior to the coronavirus disease 2019 pandemic (control). Interventions: None. MEASUREMENTS AND Main Results: We included 384 patients in the analysis. Inpatient mortality was significantly higher in patients with coronavirus disease 2019 secondary to acute respiratory distress syndrome infection compared with controls (64% vs 49%; p = 0.007). Despite both groups demonstrating similar ventilatory function and Sequential Organ Failure Assessment score on day 1 of intubation, with similar lung compliance throughout the study period, patients with coronavirus disease 2019 secondary to acute respiratory distress syndrome infection demonstrated progressive hypoxia compared with controls across the study period. Similarly, higher positive end-expiratory pressure levels and increased use of paralytics were observed in the patients with coronavirus disease 2019 secondary to acute respiratory distress syndrome infection group. On univariate analysis of the entire cohort, significant risk factors for inpatient mortality included coronavirus disease 2019 infection ( p = 0.007), older age ( p < 0.001), high Sequential Organ Failure Assessment score ( p = 0.003), vasopressor use ( p = 0.039), paralytic use ( p < 0.001), higher positive end-expiratory pressure levels on day 3 ( p = 0.027) and day 7 ( p < 0.001), in addition to acute respiratory distress syndrome severity on both days 3 ( p = 0.008) and 7 ( p < 0.001). Multivariate analysis identified coronavirus disease 2019 infection (odds ratio, 1.939; p = 0.021), older age (odds ratio, 1.042; p < 0.001), paralytic use (odds ratio, 3.366; p < 0.001), and higher Sequential Organ Failure Assessment score (odds ratio, 1.152; p = 0.027) as significant predictors of mortality across the entire cohort. Conclusions: Patients with coronavirus disease 2019 secondary to acute respiratory distress syndrome infection demonstrated higher mortality compared with control patients hospitalized with acute respiratory distress syndrome prior to the pandemic, with progressive hypoxia throughout the study period, despite similar lung mechanics and initial Sequential Organ Failure Assessment score. Coronavirus disease 2019 infection, older age, paralytic use, and higher Sequential Organ Failure Assessment scores were independent risk factors for 28-day mortality across the entire cohort.